The Application of The C4.5 Algorithm Method Calculation The Number of Sales of Paving Production on CV. SR Lamongan - Agus Setia Budi; Muhammad Hasan Wahyudi (Universitas Nusantara PGRI Kediri, 2026)
Paving production is essential for ensuring proper road infrastructure for the community. The amount of paving demand in each month is uncertain, so it is challenging for company owners to maintain optimal inventory levels to maximize profits. The purpose of this research is to design a decision support system (SPK) to help company owners determine sales decisions in the future and make it easier to decide whether or not the paving sales are in demand. The method used in this study is the C4.5 Algorithm method. From the results of this study, it was found that the C4.5 Algorithm method is the most appropriate method in determining sales decisions in the next period. The sample used is data from CV. SR Lamongan has been in sales for the last 2 years. There are 25 paving production data used for the sample. From there, the recommended method in calculating sales in the following year can be obtained, namely using the C4.5 Algorithm method due to its higher accuracy rate, achieving up to 76%.